COMPARATIVE CHARACTERISTICS OF MODERN THERMAL INSULATION TECHNOLOGIES OF BUILDINGS - І.N. Babiy; L.V. Kucherenko; Yu.S Sokolan; А.S. Zalogina; Sławomir Rabczak (Journal of Civil Engineering, Environment and Architecture, 2021)
Thermal insulation materials and technologies for thermal insulation of houses were investigated. The widespread use of such materials is due to the saving of fuel and energy resources, in particular, during the operation of buildings and structures. The subject of the analyzed stage of the research is the use of modern thermal insulation materials in construction, comparative characteristics of materials and processes associated with thermal insulation technologies.A list in the form of a table of the most used on the Ukrainian thermal insulation materials with comparative characteristics was considered. The most optimal from the point of view of ecology are ecowool, foam glass and mineral wool. The disadvantages of materials are the high cost of work and installation. Polyurethane foam, relative to other heat-insulating materials, has a minimum thermal conductivity. Also, along with glass wool, it is an excellent sound insulating material. The main requirements for thermal insulation materials are fire resistance. All listed materials correspond to this characteristic, except for expanded polystyrene.The construction industry in Ukraine is dependent on the country's economic factors. Back in 2015, there was a sharp decline in the market volume associated with an unstable political and economic situation. However, a year later, the pace of construction work has noticeably accelerated by 13,1%. This is due to the growth of the real estate market, the level of purchasing power, the popularization of energy-efficient construction in the country, and, therefore, the latest technologies and innovations in the direction of energy-saving materials.